1987
DOI: 10.1557/proc-112-159
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Radionuclide Migration Experiments at a Scale of 1 m

Abstract: Results are presented from a migration experiment carried out in a natural fracture in a 1 m × 1 m × 0.6 m quarried granite block. Near-uniform flow in the fracture was achieved by controlling the groundwater flow from the fracture laterally across the exit face of the fracture. The longitudinal dispersion was determined from the elution profile of uranine, a non-sorbing tracer. The effect of matrix diffusion was determined by reducing the linear velocity of the transport solution from approximately 3 to 0.75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Although information is available on migration processes in porous systems [1 -3], there has been little work on the study of migration in fractured media [4][5][6][7][8][9]. Most of this deals with matrix diffusion tests and transport experiments of non-reactive tracers both in-situ and at laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…Although information is available on migration processes in porous systems [1 -3], there has been little work on the study of migration in fractured media [4][5][6][7][8][9]. Most of this deals with matrix diffusion tests and transport experiments of non-reactive tracers both in-situ and at laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…Static sorption experiments indicate an increase in K a values as a function of the time allowed for partitioning [e.g., Vandergraaf and Drew, 1991 ]. As a result, the amount of retardation is often strongly affected by the residence time in the fracture [Vandergraaf et al, 1988]. We are currently investigating under which transport conditions the local equilibrium assumption can be invoked for surface sorption in a single fracture.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Dispersion of conservative and ideally sorbing solutes in a constant-aperture fracture has been described using analytical techniques [Kessler and Hunt, 1994], numerical simulations [Wels, 1995], and migration experiments [Vandergraaf et al, 1988;Fujikawa et al, 1993]. Vandergraaf et al [1988] noted that for a continuous injection of tracer into a sawed fracture in granite, dispersion of cesium was considerably greater than that for a conservative tracer. They suggested that deviations from the linearity and reversibility of the sorption process could have resulted in front sharpening or tailing of the elution profile.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative analysis of the breakthrough curves was not presented. Fujikawa et al [1993] performed migration experiments similar to those of Vandergraaf et al [1988], using pulse injections of cesium. They noted a strong dependence of the breakthrough curves, in particular peak height and tailing, on the fluid velocity in the fracture.…”
Section: Introductionmentioning
confidence: 99%